Environmental Sanitation Assessment and the Presence of Rats in Belawan Seaport, Port Health Office, Medan - Damanik, Roynaldo; Nababan, Donal; Sitorus, Mido Ester J. (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
Environmental sanitation is an activity carried out by the community to maintain and control environmental conditions with the aim of avoiding disease. Rats are one of the animals that can transmit disease The objective of this research is to find out the environmental sanitation and the presence of rats in the Class I Seaport Health Office in Belawan, Medan. This is a Descriptive Survey Research and the variables used in this research are warehouse sanitation, the signs of rats’ existence, the number and types of rats and efforts to control them, and the presence of rats in the arehouse. Data analysis in this research is carried out manually and guided by SOP (Standard Operating Procedure), warehouse sanitation checking, survey, and rat control in the Class I Seaport Health Office (KKP) Medan. Based on the result, the research shows that the first warehouse meets the requirement of sanitation, and rats’ existence is identified by the presence of rats in the three warehouses. Meanwhile, in terms of the number and types of rats, it is found that there is a mouse found in the second warehouse, success trap value is 7 % indicating that the rat density is high in the second warehouse and the types of rats found are house rats (Rattus Tanezumi). The rat control is carried out by setting a live trap. ft is suggested that the warehouse owner pay attention to and manage the environmental sanitation in the Belawan seaport warehouse by improving the outdoor environment, rooms in the building, clean water supply, and waste management.